EXPERIMENTAL INVESTIGATION OF WATER EXIT UNDER HYDROPHOBIC EFFECTS - Guzel, Bulent; Korkmaz, Fatih C. (AMER SOC MECHANICAL ENGINEERS, 2016)
Prediction of hydrodynamic loads during water exit of a body is of a great importance in designing the marine vehicles that take off from the free water surface such as sea planes and wing-in-ground effect vehicles (WIG), and that pierce through the free surface like missiles and submarines. The results of an experimental investigation on water exit of two different geometries, sphere and flat plate, with hydrophobic surfaces are presented in this paper. With and without the hydrophobic effects present, different fluid dynamics phenomena like free surface evolution, deformation and break up of free surface, wave generation, splash, air entrapment and water detachment from the solid surfaces during a water exit event have been examined. The non-dimensional exit coefficient, C-e is a function of the total vertical hydrodynamic force which depends on the geometry of the object and the hydrodynamic conditions along with the water parameters. Our study is aimed at understanding and modeling the nonlinear free surface effects and the dynamics of water exit under an extended range of parameters including hydrophobic effects. In this study, due to lack of the experimental data on the water exit problem in literature, water exit tests have been set up, first for initially partially immersed spheres and flat plates, with their center above the free surface, to be towed vertically from the water surface at various speeds. Secondly, buoyancy driven water exit of a fully immersed sphere is investigated. It is observed that when the sphere rises up, it first starts deforming the free surface, and then pierces into it. The thin water layer attached to the surface of the sphere is drawn back to the test tank as the sphere moves further upward. This causes breaking of the free surface, air entrapment and wave generation in the water tank. From digital images captured using a high speed camera, free surface breakup and water detachment at different velocities are observed and the time evolution of the water detachment and the exit characteristics are measured during a water exit event. The position of the sphere and its velocity are plotted against time. A detailed measurement of the global loads on the test objects during exit is carried out by employing strain gauges. We also showed the effects of water detachment on the test bodies during exit and after fully exited via strain gauges. All this data is also collected under the hydrophobic effects, to show how the change in surface characteristics would have significant impacts on the water exit phenomenon. Analyzing the difference in occurrence of water flow separation, the change in kinetic energy of the fluid and the free surface deformation under the hydrophobic effects may help give a better explanation of the phenomena observed during water exit and improve the design characteristics of marine structures for a water exit event.
Keywords: CIRCULAR-CYLINDER; FREE-SURFACE; MOTION; Engineering